Does GPs' self-perception of their professional role correspond to their social self-image?: A qualitative study from Germany - Natanzon, Iris; Ose, Dominik; Szecsenyi, Joachim; Campbell, Stephen; Roos, Marco; Joos, Stefanie (BMC family practice, 2010)
There is a decline in the relative numbers of general practitioners in Germany. Earlier research showed that the professional relationship between general practitioners and specialists is overshadowed by conflicts which could influence medical students not to choose a career in general practice. The aim of the study is to analyse potential discrepancies between general practitioners' self-perception of their professional role and their social self-image in relation to medical specialists and to identify potential barriers that might prevent medical students from becoming a general practitioner.
Gesehen am 05.05.2023